The Antithrombotic Effect of Recombinant Neorudin on Thrombi - Liu YB; Zhang L; Zhou XC; Zhou Y; Liu Y; Zheng C; Xu X; Geng PP; Hao CH; Zhao ZY; Wu CT; Jin JD (Dove Medical Press, 2022)
Yu-Bin Liu,1 Lin Zhang,1 Xing-Chen Zhou,1 Ying Zhou,1 Yun Liu,1 Can Zheng,1 Xiao Xu,1 Pan-Pan Geng,1 Chun-Hua Hao,2 Zhuan-You Zhao,2 Chu-Tse Wu,1 Ji-De Jin1 1Department of Experimental Hematology and Biochemistry, Beijing Institute of Radiation Medicine, Beijing, 100850, People’s Republic of China; 2Center for Pharmacodynamic Research, Tianjin Institute of Pharmaceutical Research, Tianjin, 300462, People’s Republic of ChinaCorrespondence: Chu-Tse Wu; Ji-De Jin, Department of Experimental Hematology and Biochemistry, Beijing Institute of Radiation Medicine, No. 27 Taiping Road, Beijing, People’s Republic of China, Tel +86 1086-68158312 ; +86 1086-66931425, Email wuct@bmi.ac.cn; jinjide505@163.comIntroduction: Recombinant neorudin (EPR-hirudin, EH) was developed through the addition of an EPR (Glu-Pro-Arg) peptide to the amino terminus of hirudin, which can be recognized and cut by coagulation factors XIa (FXIa) and/or Xa (FXa). In this study, the low-bleeding antithrombotic effects of EH were evaluated utilizing experimental models of thrombosis in rabbits and rats to provide a test basis for clinical trials.Methods: The bleeding risks of EH and hirudin were first compared in mice by the tail-clipping method, and then the antithrombotic activity of EH was investigated in a rabbit model of arteriovenous bypass thrombosis and a rat model of thrombotic cerebral infarction.Results: In mice, intravenous administration of EH at 1.5 mg/kg and 3 mg/kg did not affect the bleeding time compared with normal saline, while the administration of hirudin at 1.5 mg/kg prolonged the bleeding time by over 3 times the administration of normal saline. Furthermore, intravenous administration of EH had a significant dose-dependent inhibitory effect on the formation and development of arteriovenous bypass thrombosis and thrombotic cerebral infarction. Compared with an equimolar dose of hirudin, the antithrombotic effect of EH was similar, while the bleeding side effects were significantly attenuated. Moreover, when the antithrombotic effects were similar, EH had a shorter bleeding time and was associated with less bleeding than low molecular weight heparin (LMWH). EH had a therapeutic effect on thrombotic cerebral infarction without increasing the occurrence of cerebral hemorrhage.Conclusion: The findings from the preclinical animal models used in this study showed that EH could not only effectively inhibit thrombus formation but also reduce the risk of bleeding.Keywords: recombinant neorudin, hirudin, antithrombotic effect, bleeding